Atypical employment and flexicurity - Berndt Keller; Hartmut Seifert (Management Revue, 2005)
Hitherto, discussion of flexicurity has focused on normal employment (Normalarbeitsverhältnis), with atypical work receiving only cursory attention. This paper attempts to remedy this conceptual oversight by identifying strategies for reducing the social risks. We begin by analysing the two components that make up flexicurity. Therefore, we draw on the conceptual framework of forms of flexibilization. As far as social security is concerned, we propose a set of criteria that take into account shortterm and long-term effects. We then describe the different forms of atypical work and their development since the 1980s. It is necessary to establish which individuals are particularly affected. Then we discuss the extent to which the individual forms are not just atypical but also precarious. Finally, we offer further reflections on the concept of flexicurity.
Keywords: 650; atypical emplyoment; flexicurity; flexibilization; flexibility; Normalsarbeitsverhältnis; Ungeschützte Beschäftigung; Arbeitsmarktflexibilität; Flexicurity